The Rise of Alternative Accommodation: Assessing the Investment Potential of Short-Term Rental Properties in Global Cities - Dr Hemachandran Ravikumar,; Leela Sengottuvelu, (IJRDO - Journal of Business Management, 2025)
The emergence of short-term rental (STR) platforms such as Airbnb, Vrbo, and Booking.com has triggered a transformative shift in the global lodging and real estate investment sectors. Offering more personalized, flexible, and locally immersive experiences, STRs are increasingly preferred over traditional hotel accommodations. This paradigm shift is reshaping investor strategies in metropolitan real estate markets, prompting a re-evaluation of traditional income models. This study explores the investment viability of STRs in prominent global urban centers, with particular emphasis on cities across India, Thailand, and the European Union, which have shown dynamic STR market behavior and regulatory evolution. The objective of this research is to assess the financial, regulatory, and social dimensions of STR investments through a mixed-methods approach. Quantitative data was obtained from platforms like AirDNA, Airbtics, and OECD housing reports, while qualitative insights were derived from interviews with STR investors and regional industry stakeholders. Metrics such as occupancy rate, revenue per available rental (RevPAR), operational costs, and legal compliance frameworks were analyzed to identify key factors influencing profitability and sustainability of STRs in different urban contexts.In India, cities like Mumbai, Goa, Bengaluru, Delhi, Jaipur, and Kochi are experiencing a domestic travel boom and rising middle-class spending power, translating into heightened STR demand. Regulatory control remains fragmented, with limited government registration and tax clarity, though emerging collaborations between platforms and government bodies suggest impending formalization. Thailand’s market is characterized by strong seasonal demand in tourism hotspots like Phuket, Chiang Mai, and Krabi. While earlier regulations prohibited STR operations under hotel laws, recent legislative amendments now permit small-scale operators, indicating a gradual shift towards regulated growth.In the European Union, STR dynamics are highly localized. Cities like Lisbon and Prague continue to attract investor interest due to favorable returns and lighter enforcement. Conversely, Berlin and Paris enforce stringent STR regulations, including rental caps and short-term occupancy limits, reflecting concerns over housing affordability and urban gentrification. Athens offers a middle-ground regulatory environment with capped property ownership and simplified tax regimes. Despite the diverse policy landscape, a common trend is emerging toward greater transparency, accountability, and host registration.The research further highlights several operational challenges, including high running costs (up to 50% of revenue in some regions), seasonality-induced occupancy fluctuations, and legal risks associated with non-compliance. However, stress-testing models using conservative assumptions indicate that, even under low occupancy scenarios (~50%) and high operational costs, certain STR markets remain financially viable. Strategic recommendations for investors include diversifying portfolios across cities with differing risk profiles, considering hybrid rental models (e.g., mid-term rentals), and maintaining strict legal compliance to avoid penalties and long-term disruptions.The study concludes that STRs represent a compelling investment opportunity in many global urban environments, especially where tourism demand aligns with supportive or evolving regulation. Successful STR investment depends on a multidimensional approach that blends real estate insight with hospitality management and legal diligence. As cities across the world continue to redefine their regulatory stance on alternative accommodations, early-stage adaptability and regulatory foresight will determine long-term investor success.This paper contributes to the growing body of literature on real estate innovation and STR markets by offering updated comparative insights across diverse geographies. It also serves as a practical guide for new and existing investors seeking to navigate the complex, evolving landscape of global short-term rental property investment.